Light‐Activated Liquid Crystalline Hierarchical Architecture Toward Photonics. Issue 16 (27th May 2019) - Ma, Ling‐Ling; Hu, Wei; Zheng, Zhi‐Gang; Wu, Sai‐Bo; Chen, Peng; Li, Quan; Lu, Yan‐Qing
Abstract: Hierarchical architectures are of vital importance in materials science and nanotechnology. Among various building blocks, liquid crystals (LCs) have attracted particular attention due to their excellent controllability of self‐assembly behavior and the resultant physical properties. In recent years, interest in light‐activated LC hierarchical superstructures has emerged for a wide range of applications beyond LC displays. This report consists of two main parts: the light‐activated LC hierarchical architectures and their corresponding photonic applications. In the first part, different smectic layer curvature controlling methods are introduced to produce periodic defect arrays. By taking the advantages of photoalignment techniques and light‐driven molecular motors, cholesteric LC helical superstructures are highly manipulated, including pitch tuning, helix rotation, and chirality inversion. As a mutually concerned scientific issue, the photoresponsive properties of blue phase (BP) hierarchical superstructures are also introduced, enabling unique BP materials and devices driven by a facile light stimulation. Moreover, traditional optics (microlens and beam steering) and advanced photonics (specific optical field generation and LC lasers) are reviewed in the second part. It is believed that the developments introduced here can open a door for the concept of " smart optical materials " based on the self‐assembled soft LC superstructures. Abstract : Recent progresses on various hierarchical architectures in smectic, cholesteric, and blue‐phase liquid crystals (LCs) are reviewed, especially light‐activated hierarchical architectures. Corresponding applications such as microlens arrays, beam steering, specific optical field generation, and LC lasers are also presented. This report may provide a comprehensive understanding on light‐activated LC hierarchical architectures and their optics and photonics applications.